The Effect of a Blended Learning Project Based Learning Model on Scientific Attitudes and Science Learning Outcomes - I Nyoman Tika; I Gusti Ayu Tri Agustiana (Jurnal Ilmiah Sekolah Dasar, 2021)
The COVID-19 pandemic requires learning to use an online system. However, there are still many teachers who have difficulty designing appropriate learning for students. This study analyses the project-based learning model assisted by blended learning on scientific attitudes and science learning outcomes—the research population with as many as 184 students. The research sample amounted to 61 students—sampling using the random sampling technique. The design uses Post-test Only Control Group Design. Scientific Attitude data was collected using a questionnaire, and science learning outcomes were collected through an objective test. Data were analyzed through descriptive statistics and the SPSS-17 Manova test. The results showed a significant difference in scientific attitudes between students who followed the project-based learning model assisted by blended learning and students who followed the conventional learning model, with an F value of 471.8. There is a significant difference in science learning outcomes between students who follow the project-based learning model assisted by blended learning and students who take conventional learning, as evidenced by the science learning outcomes with an F value of 3.69. There are differences in scientific attitudes and science learning outcomes simultaneously between students who follow the project-based learning model assisted by blended learning and students who follow the conventional learning model. a significance level of 0.05 resulted in a p < 0.05. It can be concluded that the Project-based Blended Learning learning model can improve scientific attitudes and student learning outcomes.